Factors Influencing the Intentions of Non-Muslims in India to Accept Islamic Finance as an Alternative Financial System - Baber, Hasnan (Journal of Reviews on Global Economics, 2018)
This study aims to investigate the impact of attitude & behaviour, subjective norms and religiosity on intention to accept Islamic finance as an alternative financial system in India. An adopted questionnaire with 20 items was used to gather data from 932 respondents. The sample was taken from north India and three religions: Hindu, Christianity and Sikhism acted as strata for this study. The data was tested for association between three variables on intention to accept Islamic finance. Statistical tools like reliability analysis, independent variable correlation, sample adequacy and regression analysis were used. The findings of this study suggest that subjective norms and religiosity is the influencer in accepting Islamic finance as an alternative. Attitude & behaviour has no relevance in developing intentions about accepting Islamic Finance. The research is original and its implications will be helpful for targeting non-Muslim customers with customized products and create awareness among people that Islamic finance is not only for Muslims.